2015
DOI: 10.1016/j.joep.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Certainty and overconfidence in future preferences for food

Abstract: We examine consumer certainty of future preferences and overconfidence in predicting future preferences. We explore how preference certainty and overconfidence impact the option value to revise today's decisions in the future. We design a laboratory experiment that creates a controlled choice environment, in which a subject's choice set (over food snacks) is known and constant over time, and the time frame is short --subjects make choices for themselves today, and for one to two weeks ahead. Our results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Directly after answering this prediction question, participants answered a question assessing their certainty about their response (0-100 sliding scale, anchored from 0-"not certain at all" to 100-"extremely certain"). Previous work has used a similar self-report approach to measure certainty and confidence (Balakrishnan & Ratcliff, 1996;Bradley, 1981;Thunström et al, 2015). After completing both blocks of dependent variables, participants answered an exploratory question that elicited individual-level certainty distributions for the number of their group members contributing.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…Directly after answering this prediction question, participants answered a question assessing their certainty about their response (0-100 sliding scale, anchored from 0-"not certain at all" to 100-"extremely certain"). Previous work has used a similar self-report approach to measure certainty and confidence (Balakrishnan & Ratcliff, 1996;Bradley, 1981;Thunström et al, 2015). After completing both blocks of dependent variables, participants answered an exploratory question that elicited individual-level certainty distributions for the number of their group members contributing.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…Many studies have found that decision makers with high confidence are likely to overestimate the accuracy of their judgment – a phenomenon called overconfidence (Lichtenstein et al , 1977; Doherty et al , 1979; Harvey, 1997; Klayman et al , 1999; Fellner and Krügel, 2012; Fellner-Röhling and Krügel, 2014; Thunström et al , 2015; Merkle, 2017). Moore and Healy (2008) and Bazerman and Moore (2008) found three principal forms of overconfidence: over-estimation of one’s actual performance; over-placement of one’s performance compared to others’; and over-precision about the accuracy of one’s judgment.…”
Section: Manifestations Of Bias In Cpdrmentioning
confidence: 99%
“…For instance, consumer preferences are influenced by the social setting in which the product is being used (i.e., the preference may be affected by who else uses this product); the proportion of people in the actor's social network that consumes this product (the so-called "socialization effect"); and the intensity of preference for a product that is repeatedly being consumed (a process known as "exposure effect") (see Janssen and Jager 2001 for a detailed discussion). In addition, preference uncertainty may be related to overconfidence in forecasting individual future preferences that lead to errors in predictions of future consumption (Thunström et al 2015). Uncertainty of future preferences is also attributed to incorrect predictions of feelings that have been found to impact consumer behavior, e.g., (Loewenstein and Schkade 2003;MacInnis et al 2005).…”
Section: Framing the Problem Of Future Preference Uncertaintymentioning
confidence: 99%
“…When it comes to environmental amenities in particular, preference uncertainty may be explained by the random state of nature, the uncertainty of future income, or the unfamiliarity with the good (Thunström et al 2015). To wit, the non-market value refers to small changes in the state of the environment and not the state of the environment itself (TEEB 2010).…”
Section: Framing the Problem Of Future Preference Uncertaintymentioning
confidence: 99%